Indian Commodity Market Trends: Growth, Challenges, and Future Outlook - Sonia; Tilak Raj (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
This paper delves into the shifting dynamics of the Indian commodity market, examining its growth trajectory, current challenges, and future opportunities. The study also assesses the impact of technological advancements, government regulations, and global market shifts on India's commodity trade. The purpose of this research is to examine the recent trends in India's commodity market, identifying key growth drivers and challenges that influence its development. This research underscores the importance of factors like supply-demand dynamics, global market trends, and macroeconomic conditions in shaping commodity prices in India. Finally the study provided valuable suggestions. It is stated that geopolitical factors and climate change introduce further complexities that stakeholders must address.